ENGLISH TEACHER PERFORMANCE IN TEACHING LEARNING PROCESS DURING PANDEMIC COVID-19 AT DUTA HARAPAN SCHOOL MEDAN. - Damanik, Harianty Harapanta; Sinaga, Nenni Triana (IKIP PGRI Bojonegoro, 2022)
Abstract: The aim of the research was to find out the English Teacher Performance in Teaching Learning during Pandemic Covid-19. The subject was the teachers of Duta Harapan School Medan who tough through English Language. This research applied the anthropolinguistic approach. The data were the utterances of teachers while they were in online teaching. The analytical research used interactive model with three interactive steps, namely: data condensation, data display and drawing/verifying conclusion. The results of this research showed that the teacher’s performance in teaching English during the pandemic were quite good. The teachers had different tribes, social class and background. They showed different performances that used to convey the knowledge through explaining, advising, reminding, persuading and motivating. The performance was divided into opening, core and closing activities. There were found paralinguistic, kinesics, and material elements on the teacher’s performance. The teacher’s performance encouraged and motivated the students to study. Virtual meeting forced the teacher to upgrade their own ability, technologies, learning facilities, and speaking skill to attract student’s interest. The creative activities teacher appreciated the students’ contribution and activeness. The teacher show smiling face, happy face and clap the hands when the student did good effort. Keywords: English teacher, Performance, Pandemic, Anthropolinguistic approach. Abstrak: Tujuan penelitian ini adalah untuk mengetahui performansi Guru Bahasa Inggris dalam Pembelajaran Mengajar selama Pandemi Covid-19. Subjek penelitian ini adalah guru-guru Bahasa Inggris di Sekolah Duta Harapan Medan. Penelitian ini menggunakan pendekatan antropolinguistik. Data adalah ucapan-ucapan guru saat guru mengajar online. Analisis penelitian menggunakan model interaktif dengan tiga langkah interaktif, yaitu: kondensasi data, penyajian data dan penarikan/verifikasi kesimpulan. Hasil penelitian ini menunjukkan bahwa performansi guru dalam mengajar bahasa Inggris selama pandemi cukup baik. Para guru berasal dari suku, kelas sosial dan latar belakang yang berbeda. Mereka menunjukkan performansi yang berbeda untuk menyampaikan pelajaran seperti menjelaskan, menasihati, mengingatkan, membujuk dan memotivasi. Performansi yang ditemukan terdiri atas: pembuka, inti dan penutup. Terdapat unsur paralinguistik, kinesik, dan materi pada performansi guru. Performansi guru mendorong dan memotivasi siswa untuk belajar. Pertemuan virtual memaksa guru untuk meningkatkan kemampuan, teknologi, fasilitas belajar, dan keterampilan berbicara mereka sendiri untuk menarik minat siswa. Kegiatan kreatif menciptakan pembelajaran aktif sehingga guru menghargai kontribusi dan keaktifan siswa. Guru menunjukkan wajah tersenyum, wajah bahagia dan bertepuk tangan ketika siswa melakukan usaha yang baik. Kata kunci: Guru Bahasa Inggris, Performansi, Pandemi, Pendekatan Antropolinguistik.